Analisis Subsektor Tanaman Pangan di Kabupaten Siak Provinsi Riau - Marpaung, Minaria Dahliana; Edwina, Susy; ', Yusmini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The conversion of food crops to oil palm plantation becomes a critical issue in Riau Province. There are less and less available land for food crops. The aim of this research are to (1) identify the potential subsector of food crops in Siak; (2) to analyze the sector basis and non basis commodity of food crops; (3) identify relatives spreading and coefficient specialist of basis subsector of food crops; (4) and analyze the feasibility of food crops on economic aspect. The study used descriptive to the wide of harvest and products, LQ, the coefficient location, specialist coefficient and RCR. The source result of subsector food crops in Siak has analyze potential in descriptive to be progessed are rice paddy field, cassava, and corn. LQ shows that the food plants is basis sector in Siak with close mark LQ of the wide harvest and product is wet rice field. The coeffient of location shows the activities farming of food crops in Siak spread in some subdistricts. The specialist coefficient in Siak did commodity in certain food plants are done by the farmer in each subdistrict still has variety. In economist farmer effort food crops wet rice field in Siak suibtable to be progressed, this is showed with RCR mark. Â  Keywords: Coeffcient location, coeffcient specialist, food crops, LQ